The Level of Confidence of Tirtajaya Vocational High School Students in Taekwondo Extracurricular Activities - Evi Susianti; Tedi Purbangkara (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine how high the confidence level of the Tirtajaya Vocational High School is in participating in taekwondo extracurricular activities. This study uses a quantitative approach. If viewed from the type of data presented, the method in this study is a survey research using a questionnaire. The sample used was a total sampling of 25 students. The results of the research on the level of confidence of Tirtajaya Vocational High School students in participating in taekwondo extracurricular activities obtained the lowest score (minimum) 48.8, the highest score (maximum) 72.8, the average score (mean) 59.3 and the standard deviation (SD) 6,9. Based on the results of calculations by processing research data, it can be concluded that the Confidence Level of Tirtajaya Vocational High School students in participating in Taekwondo Extracurricular Activities is in the LACK category with an average percentage of 59.34%.